Effect of spiritual intelligence, emotional intelligence, psychological ownership and burnout on caring behaviour of nurses: a cross-sectional study - Devinder Kaur; Murali Sambasivan; Naresh Kumar (2013)
Aims and objectives. To propose a model of prediction of caring behaviour among nurses that includes spiritual intelligence, emotional intelligence, psychological ownership and burnout. Background. Caring behaviour of nurses contributes to the patients’ satisfaction, well-being and subsequently to the performance of the healthcare organisations. This behaviour is influenced by physiological, psychological, sociocultural, developmental and spiritual factors. Design. A cross-sectional survey was used, and data were analysed using descriptive statistics and structural equation modelling. Methods. Data were collected between July–August 2011. A sample of 550 nurses in practice from seven public hospitals in and around Kuala Lumpur (Malaysia) completed the questionnaire that captured five constructs. Besides nurses, 348 patients from seven hospitals participated in the study and recorded their overall satisfaction with the hospital and the services provided by the nurses. Data were analysed using structural equation modelling (SEM). Results. The key findings are: (1) spiritual intelligence influences emotional intelligence and psychological ownership, (2) emotional intelligence influences psychological ownership, burnout and caring behaviour of nurses, (3) psychological ownership influences burnout and caring behaviour of nurses, (4) burnout influences caring behaviour of nurses, (5) psychological ownership mediates the relationship between spiritual intelligence and caring behaviour and between emotional intelligence and caring behaviour of nurses and (6) burnout mediates the relationship between spiritual intelligence and caring behaviour and between psychological ownership and caring behaviour of nurses. Conclusions. Identifying the factors that affect caring behaviour of nurses is critical to improving the quality of patient care. Spiritual intelligence, emotional intelligence, psychological ownership and burnout of nurses play a significant role in effecting caring behaviour of nurses. Relevance to clinical practice. Healthcare providers must consider the relationships between these factors in their continuing care and incorporation of these in the nursing curricula and training.